Transformasi Literasi Digital dengan Canva Sebagai Langkah Strategis Untuk Penguatan Pendidikan dan Pemberdayaan Potensi Desa Susukan - Rahma Widiantie; Handayani Handayani; Ina Setiawati; Huda Farid Nurrohman (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
The community service program titled “Digital Literacy Transformation through Canva as a Strategic Step for Strengthening Education and Empowering the Potential of Susukan Village toward Independence” was implemented to enhance the digital literacy competencies of rural communities, particularly among youth. This initiative was motivated by the low level of digital-based educational literacy, limited use of interactive learning media, and the lack of promotional content supporting the creative economy in Susukan Village. The implementation method employed a community-based empowerment approach through five main stages: socialization, training, technology application, mentoring and evaluation, and the establishment of the Village Digital Literacy Center. The training was conducted through hands-on practice, including the introduction of basic Canva features, the creation of interactive learning media, and the development of village branding content. The results demonstrated a significant improvement in participants’ skills: 80% were able to produce at least three usable designs, 72% successfully created independent educational or promotional content, and participant satisfaction reached 91%. Moreover, participants’ digital literacy scores increased to 82.4 after the training. The establishment of the Village Digital Literacy Center serves as a strategic step to ensure program sustainability and autonomous knowledge transfer at the local level. Overall, this activity successfully promoted digital literacy transformation in Susukan Village, strengthened the community’s ability to utilize technology for education and local potential empowerment, and fostered an adaptive and self-reliant village in the digital era.